2017
DOI: 10.1111/jopy.12307
|View full text |Cite
|
Sign up to set email alerts
|

How Do Different Ways of Measuring Individual Differences in Zero‐Acquaintance Personality Judgment Accuracy Correlate With Each Other?

Abstract: Different ways of measuring individual differences in personality judgment accuracy are not conceptually and empirically the same, but rather represent distinct abilities that rely on different judgment processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 47 publications
1
32
0
Order By: Relevance
“…We do not claim this would always be the case because there are situations where falling back on stereotypes (or base rates) might sometimes improve accuracy (Lewis, Hodges, Laurent, Srivastava, & Biancarosa, ). In fact, in some ways of measuring accurate personality judgment, making use of stereotypes (i.e., using normative knowledge) is an integral part of achieving accuracy (Hall et al, in press).…”
Section: Integrative Frameworkmentioning
confidence: 99%
“…We do not claim this would always be the case because there are situations where falling back on stereotypes (or base rates) might sometimes improve accuracy (Lewis, Hodges, Laurent, Srivastava, & Biancarosa, ). In fact, in some ways of measuring accurate personality judgment, making use of stereotypes (i.e., using normative knowledge) is an integral part of achieving accuracy (Hall et al, in press).…”
Section: Integrative Frameworkmentioning
confidence: 99%
“…As shown by Hall et al ( 2018 ), trait accuracy, overall profile accuracy, and distinctive profile accuracy are not interchangeable measures. For instance, single-trait accuracies show only low correlations with each other and with other accuracy types ( Hall et al 2018 ). These authors also suggested that different mechanisms and cognitive demands may be involved in different accuracy types.…”
Section: Introductionmentioning
confidence: 97%
“…Another important aspect to consider when assessing personality judgment accuracy (and its correlates) is that it can be calculated in different ways using the same data (e.g., Back and Nestler 2016 ; Hall et al 2018 ; Letzring and Funder 2018 ). The first accuracy type is trait accuracy , which refers to the ability to discriminate among different targets on one given trait (e.g., to evaluate whether person A is more or less agreeable than person B), thus requiring inter-target comparisons ( Hall et al 2018 ). Trait accuracy is typically calculated by correlating judges’ ratings across targets on a given trait with the targets’ self-rated score on this trait (e.g., Lippa and Dietz 2000 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, this is one of the only studies that focused specifically on the accuracy as the main aim of the study, and therefore reported on different types of accuracy (the self-other agreement and the agreement between multiple raters). It can be observed that the very concept of accuracy and its magnitude varies in the case of the measures used, and in this study, accuracy is presented with multiple measures, and thus the outcome of personality judgment is more fully illustrated (Hall et al, 2018). Third, the positive findings on personality judgement accuracy by non-experts open up a question on the nature of the ability to judge one's personality, that should be further explored.…”
Section: Discussionmentioning
confidence: 79%